Sport in Ireland, 1600-1840 - Kelly, James, 1959- (Four Courts Press, 2014)
This title examines all the main sports played in Ireland over a period of nearly 250 years, from the beginning of the 17th century to the onset of the Famine. In this era, medieval sports (such as archery and falconry) gave way to new recreations, or were restructured (hunting) in a way that met modern needs.